Exploring the Composition and Bioactivity of Hedychium flavum Leaf and Stem Essential Oil: In Vitro Assessment of Antibacterial, Antioxidant, Cytotoxicity, and Enzyme Inhibitory Activities - Furong Ding; Xia Wu; Nian Yang; Jingming Niu; Yi Hong; Minyi Tian (Journal of Chemistry)
Hedychium flavum is an edible, medicinal, and aromatic plant widely cultivated for its essential oil. So far, little studies have been done on its phytoconstituents and bioactivities. Hence, the research aimed to determine the chemical constituents of leaf essential oil (L-EO) and stem essential oil (S-EO) of H. flavum and first estimate their antibacterial, antioxidant, cytotoxic, and enzyme inhibitory activities. According to gas chromatography-flame ionization detector/mass spectrometer (GC-FID/MS) assay, L-EO was mainly composed of β-pinene (33.4%), α-pinene (10.4%), humulene (6.8%), β-caryophyllene (6.0%), eucalyptol (6.0%), caryophyllene oxide (5.5%), endo-borneol (3.8%), humulene epoxide II (3.7%), and D-limonene (3.2%). The predominant components of S-EO were β-pinene (17.2%), eucalyptol (9.7%), nerolidol (7.8%), α-phellandrene (6.7%), α-pinene (5.8%), β-caryophyllene (5.4%), terpinen-4-ol (4.5%), D-limonene (4.4%), p-cymene (3.7%), endo-borneol (3.5%), and α-terpineol (3.5%). For the bioactivities, L-EO and S-EO showed strong antibacterial activity against Escherichia coli, Enterococcus faecalis, and Bacillus subtilis with the minimum inhibitory concentration (MIC) of 9.77–625.00 µg/mL and the minimum bactericidal concentration (MBC) of 9.77–1250.00 µg/mL. Both L-EO and S-EO exhibited moderate antioxidant activity in the DPPH (14.52 ± 0.93 mg/mL and 4.73 ± 0.15 mg/mL, respectively) and ABTS (4.05 ± 0.75 mg/mL and 2.38 ± 0.14 mg/mL, respectively) free radical scavenging capacity. S-EO showed selective cytotoxicity on human leukemic K562 cell line (IC50 = 93.94 ± 0.91 µg/mL), which was nearly three times that of noncancer L929 cell line (IC50 = 294.49 ± 9.40 µg/mL). In enzyme inhibitory properties, L-EO exerted a potent inhibition on α-glucosidase (IC50 = 1.03 ± 0.02 mg/mL), and both essential oils had weak inhibition against cholinesterase and tyrosinase. Thus, H. flavum L-EO and S-EO possess antibacterial, antioxidant, cytotoxic, and enzyme inhibitory activities with potential for exploitation in the food, cosmetic, and pharmaceutical industries.